The Humpty Dumpty Effect on Planet Earth - Berger, Joel; Lambert, Joanna E. (Frontiers in Conservation Science, 2022)
Humans have treated the earth harshly. Degradation of extant ecosystems leaves little chance that they might function as they have in the past. Putting back the pieces and restoring what once existed is no longer possible even with re-wildling—an effect analogous to the Humpty Dumpty parable. However, we do have conservation successes after concerted efforts related to habitat protection, species and ecosystem restoration, and planning. While the changes to Earth's biosphere are grave, necessitating immediate and exhaustive action, our Humpty Dumpty world reassembles with progressive conservation victories at all regional scales from local to global which should lead to a modicum of optimism rather than despair. We suggest that to be truly effective our work as academic scientists must be more than publishing in scholarly journals. At the least, this should include changes in how success is measured in science and how university tenure is awarded.